Wheat cultivar adaptations in Rio Grande do Sul. I. Regional adaptation of early cultivars - Osório, Eduardo Allgayer; Moreira, João Carlos Soares; Silva, Enedino Corrêa da; Silva, Maurício Lima da (Pesquisa Agropecuaria Brasileira, 2014)
The research reported in this paper involved the performance of fifteen wheat cultivars in Rio Grande do Sul. All of them are compared with the most productive cultivar in each wheat region. The cultivars that presented higher general mean yields in the state had superior yields in each region, except in region I where lower general mean yield cultivars were highly productive. During 1968 to 1970 the best cultivars in the state of Rio Grande do Sul were IAS 52, Lagoa Vermelha, IAS 55, IAS 51-Albatroz, IAS 54, IAS 56 and IAS 53.